Beyond Reconstruction Plates: Load-Sharing Fixation for Complex Mandibular Fractures - I Gusti Ayu Amitia Maharani; Putu Trisna Utami (Institut Nalanda, 2026)
Mandibular fractures are common maxillofacial injuries that require stable osteosynthesis to restore occlusion, alignment, and mandibular function. Reconstruction plates are often selected for complex segmental or comminuted fractures because they provide load bearing support, yet their placement may require extensive exposure and greater soft tissue manipulation. Recent biomechanical and clinical evidence suggests that load sharing fixation with miniplates can offer sufficient stability in carefully selected cases. This case series reports two complex mandibular fractures treated with dual long 2.0 mm titanium miniplates without reconstruction plates. The first patient, a 28 year old man, had a segmental parasymphysis and corpus fracture with left subcondylar fracture and TMJ dislocation. The second patient, a 34 year old woman, had a comminuted left parasymphysis fracture extending to the corpus with contralateral condylar head fracture and TMJ dislocation. Both patients underwent open reduction and internal fixation using dual long miniplates along mandibular buttress lines. Anatomical reduction and satisfactory occlusion were achieved. Recovery was uneventful, without infection, malocclusion, or hardware failure. At two months, alignment, mouth opening, and function improved. Dual long 2.0 mm miniplates may provide a less invasive alternative when cortical contact and reduction are adequate. Future prospective studies are needed to confirm outcomes.